Preaching and harmony with other faiths |الدعوة والتآلف مع المعتقدات الأخرى - Ghilmanul Wasath (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2010)
this article taks about the preaching methode and harmony live of muslim with other faiths as the neighboor or relationship.